Islamic banking and finance teaching: a case of the Faculty of Economics in International Islamic University Malaysia (IIUM) - Kayadibi, Saim (Mehir Vakfi, 2010)
The teaching of Islamic Banking and Finance is simultaneously taught with the conventional banking system in the Faculty of Economics and Management Sciences, International Islamic University Malaysia. The faculty, which is one of the first established faculties of the University, became a centre for Islamic banking and finance soon after its establishment. Almost with its inception countless of international students have already graduated and many are still being trained to serve the Muslim nation. Islamic economics and banking must do its arguments according to Islamic principles in theory and practice. For this reason the called system must present its educational systems seriously as an alternative to the conventional banking system. The Kulliyyah responds to the shortcomings through providing these two systems simultaneously within the Faculty of Economics and Management Sciences. With this study the reflection of Islamic banking and finance in Malaysia will be elaborated via taking into consideration the International Islamic University Malaysia, the Faculty of Economics and Management Sciences with the development related works, curriculum, contents, training methods and will be reviewed and analyzed accordingly. Due to this reason, it’s expected that it would contribute new ideas to recently opening Islamic banking and finance institutions in different countries over the world with curriculum and method.